2015
DOI: 10.1128/mbio.01030-15
|View full text |Cite
|
Sign up to set email alerts
|

Genomically Informed Surveillance for Carbapenem-Resistant Enterobacteriaceae in a Health Care System

Abstract: Carbapenem-resistant Enterobacteriaceae (CRE) are an urgent public health concern. Rapid identification of the resistance genes, their mobilization capacity, and strains carrying them is essential to direct hospital resources to prevent spread and improve patient outcomes. Whole-genome sequencing allows refined tracking of both chromosomal traits and associated mobile genetic elements that harbor resistance genes. To enhance surveillance of CREs, clinical isolates with phenotypic resistance to carbapenem antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 50 publications
2
96
0
Order By: Relevance
“…coli transformants containing Tn4401a and Tn4401h variants on native parent plasmid backgrounds showed meropenem and cefepime resistance MICs compared to E. coli transformants containing Tn4401b, consistent with the variations in bla KPC expression (i.e., Tn4401a ¡ Tn4401h ¡ Tn4401b). Previous studies have suggested that another mechanism, in addition to gene expression and copy number, namely, production of porin channel defects, is a primary contributor to the variability in susceptibility in testing KPC-producing isolates (3,11,20,(28)(29)(30). Here we excluded the impact of porin channel variation on susceptibility by evaluating plasmids bearing the Tn4401-bla KPC units in a fixed E. coli background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli transformants containing Tn4401a and Tn4401h variants on native parent plasmid backgrounds showed meropenem and cefepime resistance MICs compared to E. coli transformants containing Tn4401b, consistent with the variations in bla KPC expression (i.e., Tn4401a ¡ Tn4401h ¡ Tn4401b). Previous studies have suggested that another mechanism, in addition to gene expression and copy number, namely, production of porin channel defects, is a primary contributor to the variability in susceptibility in testing KPC-producing isolates (3,11,20,(28)(29)(30). Here we excluded the impact of porin channel variation on susceptibility by evaluating plasmids bearing the Tn4401-bla KPC units in a fixed E. coli background.…”
Section: Discussionmentioning
confidence: 99%
“…To date, seven unique Tn4401 isoforms (Tn4401a to Tn4401g) have been identified (9)(10)(11)(12), with Tn4401a and Tn4401b being the most widespread (13). The original characterization of these isoforms demonstrated deletions in the noncoding region upstream of bla KPC or lacking genes or both as follows: a, Ϫ99 bp (14,15); b, no deletion (3); c, Ϫ215 bp (16); d, Ϫ68 bp (9) and Ϫ5.3 kb (9,17,18); e, Ϫ255 bp (17); f, truncated tnpA and lacking tnpR, ISKpn7 left, and Tn4401 IRL-1 (10); g, lacking tnpA, tnpR, and ISKpn7 left, with a Ϫ215-bp deletion in the noncoding region (Fig.…”
mentioning
confidence: 99%
“…This suggests that bla KPC -harboring pKp58_N-and pKm38_N-like plasmids were circulating in the Northeastern United States for almost 2 decades and may have contributed significantly to the spread of KPC at the early stages of the CRE epidemic. In addition, bla KPC -harboring IncN plasmids have been frequently reported elsewhere around the world and in other Enterobacteriaceae species (10,(25)(26)(27)(28)(29)(30), suggesting the IncN plasmid is an important vector in the dissemination of KPC. Interestingly, bla KPC in this study was identified in ST111 K. pneumoniae and K. michiganensis isolates.…”
mentioning
confidence: 99%
“…Although A. baumannii ST2 clone has been previously associated with the production of CHDLs (OXA-23, OXA-24/40 and OXA-58) and the VIM MBL, this is the first report of the identification of bla Location and characterization of the genetic environment of the bla KPC Southern blot hybridization with S1 nuclease and I-CeuI digestion revealed that the KPC gene was chromosomally encoded (data not shown). The chromosomal location of the KPC gene has been previously described from an A. baumannii from Puerto Rico (Martinez et al, 2014), one P. aeruginosa from Colombia (Villegas et al, 2007) and two K. pneumoniae from the USA (Chen et al, 2015;Pecora et al, 2015). In our isolate, KPC-2 gene was identified within a truncated version of the Tn4401e (255 bp deletion upstream of the KPC gene) in which the KPC gene is flanked by the ISKpn6 and ISKpn7 but lacks the transposase and resolvase genes (Figs 1 and 2a).…”
Section: Strain Typificationmentioning
confidence: 99%